84PCombination treatment of astragalus membranaceus, dose-modified chemotherapy, and anti-PD1 checkpoint inhibitor for patients of advanced malignancy with initial cachexia or poor performance status: A single-institute experience. (7th November 2019) - Lai, H C; Lin, W; Po, T L; Yang, M J
Abstract: Background: Cancer-related fatigue (CRF), cachexia, or poor performance status, which occurs among patients with advanced malignancy, has always frustrated clinicians and patients and been primarily managed via conservative treatments. The botanically derived drug extracted from Astragalus membranaceus(PG2) has been approved by Taiwan FDA as a standard of choice for CRF management. We show real-world practice about combination treatment of PG2, dose-modified chemotherapy, and anti-PD1 checkpoint inhibitor in patients with advanced malignancy with cachexia, fatigue, or poor performance status here. Methods: We conducted a retrospective chart review of patients with advanced malignancy with CRF or cachexia who received a combination treatment mentioned above from Dec. 2016 to Dec. 2018. Results: The medical charts of 23 patients with different malignancies who received PG2 during the systemic treatment, including chemotherapy and immunotherapy, were reviewed. The following types of cancers were detected among these patients: digestive system (n = 7), head and neck (n = 7), gynecological (n = 6), and others (n = 3). During recruitment, 22 patients had stage IV cancer. The initial ECOG performance status was 1 (n = 5), 2 (n = 11), > 2 (n = 7). The objective responses were 3 CR (13%), 13 PR (57%), 1 SD (4%), 5 PD (22%), and 1 death with treatment related tumor lysis syndrome of 6 days (4%). The median overall survival (OS) was 20.5 months (95% CI = 14.364, 26.636). The median progression-free survival (PFS) was 11.6 months (95% CI = 2.017, 21.249). Adverse events included anorexia (30%), neutropenia (26%), pneumonia (22%), nephrotoxicity (13%), and nausea and vomiting (13%). The adverse effect for grade 3/4/5 was rare. Conclusions: This retrospective study provided real-world data for the management of initially presenting CRF, cachexia, or poor performance status with PG2 injection in 23 advanced cancer patients. The treatment was relatively fair tolerated with impressive results of OS and PFS. Further prospective study of combination therapies including immunotherapy and PG2 injection is warranted for more robust evidence. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.